Ultra Petita Principle: Hadhanah Determination in Medan Religious High Court Decision No. 1/Pdt.G/2025/PTA.Mdn - Nurmala Sari; Fauziah Lubis (Hakamain: Journal of Sharia and Law Studies, 2026)
This study aims to analyze the application of the ultra petita principle under Supreme Court Circular Letter (SEMA) Number 3 of 2015 concerning the determination of child hadhanah (child custody) rights in the Medan Religious High Court Decision No. 1/Pdt.G/2025/PTA.Mdn. The study is motivated by the legal issue concerning the limits of judicial authority in determining hadhanah rights when no claim requesting such determination is submitted by the parties. This research employs a normative juridical method using statutory, case, and conceptual approaches. The findings demonstrate that the application of the ultra petita principle in Decision No. 1/Pdt.G/2025/PTA.Mdn is reflected in the panel of judges' decision to limit its authority to the claims submitted by the parties. Accordingly, the panel did not determine hadhanah rights because no petitum requesting hadhanah was included in the reconventional claim. This reasoning was based on Article 178 paragraph (3) of the Herziene Indonesisch Reglement (HIR) and the provisions of SEMA Number 3 of 2015, which prohibit judges from granting relief beyond the parties' requests unless permitted by law. Therefore, the decision consistently applies the ultra petita principle while promoting legal certainty and procedural fairness in Islamic family dispute resolution. This study contributes to the international literature on comparative Islamic family law by demonstrating how Indonesian religious courts balance judicial restraint with child custody adjudication within a pluralistic legal system, offering insights for comparative studies on judicial discretion and procedural justice in family law.